The politics and ethics of the just price : ethnographies of market exchange - Luetchford, Peter; Orlando, Giovanni A., 1963- (Research in economic anthropology, 2019)
Comprising eight case studies from around the world, this volume investigates the social, political and ethical implications of markets through the specific lens of prices. Drawing on the most recent scholarship in economic anthropology, it represents the first systematic attempt to address ethnographically the ancient debate on the ""just price.""